Effects of potassium ions on the electrical and pH gradients across the membrane of Streptococcus lactis cells. - Kashket, E R (1977)
Bacteria transduce and conserve energy at the plasma membrane in the form of an electrochemical gradient of hydrogen ions (deltap). Energized cells of Streptococcus lactis accumulate K+ ions presumably in exchange for H+. We reasoned that if the movement of H+ is limited, then an increase in H+ efflux, effected by potassium transport inward, should result in changes in the steady-state deltap. We determined the electrical gradient (deltapsi) from the fluorescence of a membrane potential-sensitive cyanine dye, and the chemical H+ gradient (deltapH) from the distribution of a weak acid. The deltap was also determined independently from the accumulation levels of the non-metabolizable sugar thiomethyl-beta-galactoside. KCl addition to cells fermenting glucose or arginine at pH 5 changed the deltap very little, but lowered the deltapsi, while increasing the deltapH. At pH 7, the deltapH only increased slightly; thus, the decrease in deltapsi, effected by addition of potassium ions, resulted in a lowered steady-state deltap. These effects were shown not to be due to swelling or shrinking of the cells. Thus, in these nongrowing cells, under conditions of energy utilization for the active transport of K+, the components of deltap can vary depending on the limitations on the net movement of protons.